Ultrasonic guided waves for monitoring corrosion in submerged plates - Sharma, S.; Mukherjee, Abhijit (John Wiley & Sons Ltd., 2014)
This paper reports a non-contact, in-situ and non-destructive corrosion monitoring methodology for submerged plates using ultrasonic guided waves. Specific surface sensitive and core sensitive guided wave modes are utilized for monitoring plates undergoing accelerated impressed current corrosion in the presence of chlorides. A combination of the selected guided wave modes could effectively discern various corrosion mechanisms occurring in plates. Along with the ultrasonic signals, mass loss, stress–strain behaviour and tensile strength of the plates at different stages of corrosion have been monitored. Algebraic relationships between the ultrasonic readings and other parameters have been developed. This investigation should be useful in developing a non-destructive technique for monitoring progressive corrosion in plates and assessing their deterioration in strength, stiffness and mass loss that would help in the estimation of residual life.